Identification of human and rodent thymic epithelium using tetanus toxin and monoclonal antibody A2B5. - Haynes, B F (1983)
Using a monoclonal antibody (A2B5), which binds to GQ ganglioside, and tetanus toxin, which binds to GD and GT gangliosides, distinct regions of human and rodent thymic epithelial cells have been identified. The lymphoid elements of the thymus do not bind A2B5 or tetanus toxin. The A2B5 and tetanus toxin-binding cells form a network of thymic epithelial cells throughout the thymic subcapsular cortex and thymic medulla and contain thymopoietin and thymosin alpha-1.